Chaperonin-Containing TCP1 Complex (CCT) Promotes Breast Cancer Growth Through Correlations With Key Cell Cycle Regulators - Ghozlan, Heba; Showalter, Adrian; Lee, Eunkyung; Zhu, Xiang; Khaled, Annette R. (Frontiers in Oncology, 2021)
Uncontrolled proliferation as a result of dysregulated cell cycling is one of the hallmarks of cancer. Therapeutically targeting pathways that control the cell cycle would improve patient outcomes. However, the development of drug resistance and a limited number of inhibitors that target multiple cell cycle modulators are challenges that impede stopping the deregulated growth that leads to malignancy. To advance the discovery of new druggable targets for cell cycle inhibition, we investigated the role of Chaperonin-Containing TCP1 (CCT or TRiC) in breast cancer cells. CCT, a type II chaperonin, is a multi-subunit protein-folding complex that interacts with many oncoproteins and mutant tumor suppressors. CCT subunits are highly expressed in a number of cancers, including breast cancer. We found that expression of one of the CCT subunits, CCT2, inversely correlates with breast cancer patient survival and is subject to copy number alterations through genomic amplification. To investigate a role for CCT2 in the regulation of the cell cycle, we expressed an exogenous CCT2-FLAG construct in T47D and MCF7 luminal A breast cancer cells and examined cell proliferation under conditions of two-dimensional (2D) monolayer and three-dimensional (3D) spheroid cultures. Exogenous CCT2 increased the proliferation of cancer cells, resulting in larger and multiple spheroids as compared to control cells. CCT2-expressing cells were also able to undergo spheroid growth reversal, re-attaching, and resuming growth in 2D cultures. Such cells gained anchorage-independent growth. CCT2 expression in cells correlated with increased expression of MYC, especially in spheroid cultures, and other cell cycle regulators like CCND1 and CDK2, indicative of a novel activity that could contribute to the increase in cell growth. Statistically significant correlations between CCT2, MYC, and CCND1 were shown. Since CCT2 is located on chromosome 12q15, an amplicon frequently found in soft tissue cancers as well as breast cancer, CCT2 may have the basic characteristics of an oncogene. Our findings suggest that CCT2 could promote cell division and be a node through which pathways involving MYC, cyclin D1 and other factors could converge. The therapeutic inhibition of CCT2 may have the potential to achieve multi-target inhibition, overcoming the limitations associated with single agent inhibitors.